Combined Optokinetic Treatment and Vestibular Rehabilitation to Reduce Visually Induced Dizziness in a Professional Ice Hockey Player After Concussion: A Clinical Case - Mucci, Viviana; Meier, Cornelia; Bizzini, Mario; Romano, Fausto; Agostino, Daniel; Ventura, Alessandra; Bertolini, Giovanni; Feddermann-Demont, Nina (Frontiers in Neurology, 2019)
Background: The appropriate detection and therapy of concussion symptoms are of great importance to avoid long-term impairment and absence from pre-concussive activities, such as sport, school or work. Post-traumatic headache is known to be a high risk of persistent symptom after a concussion, while less knowledge is currently present when considering dizziness. Dizziness has even been classified as a predictor for symptom persistence. One aspect of dizziness, which has never been considered is visually induced dizziness (VID), often develops as a consequence of a vestibular impairment. This manuscript presents the clinical case of a 25-year-old male, professional ice hockey player, whereby a therapeutic approach to VID after concussion is demonstrated. Case: A detailed interdisciplinary laboratory-assisted neurological, neurovestibular and ocular-motor examination was performed 20 days post-concussion, which indicated VID symptoms. Thus the player qualified for a 5-day combined vestibular, balance and optokinetic therapy, which aimed to reduce the player’s increased sensitivity to visual information. Each treatment day consisted of two sessions: vestibular/ocular-motor training and exposure to optokinetic stimuli combined with postural control exercises. The optokinetic stimulus was delivered in the form of a rotating disk. VID symptoms were recorded daily via posturography and a visual analogue scale prior to the optokinetic sessions. The player improved over the course of each treatment day and he was able to return to play ice hockey 15 days after the final treatment session. Three months later the player reported no symptoms in the follow up questionnaire. Conclusion: The combination of vestibular, balance and optokinetic therapy led to remission of VID symptoms in a professional ice hockey player after multiple concussions, within a short time frame after his last concussion. Thus, this case study highlights the significant benefit of treating post-concussive VID symptoms utilizing a multidisciplinary approach.